Understanding Why Nurse Practitioner (NP) and Physician Assistant (PA) Productivity Varies Across Community Health Centers (CHCs): A Comparative Qualitative Analysis. (February 2021) - Pittman, Patricia; Park, Jeongyoun; Bass, Emily; Luo, Qian "Eric"
This study asks how much and why the productivity of advanced practice clinicians (APCs; nurse practitioners and physician assistants) varies across community health centers (CHCs), as measured in their marginal contribution to overall patient visits. We found APCs in the 90th percentile CHCs provide about 1, 840 adjusted-visits per year, whereas APCs in the 10th percentile CHCs provide about 978 adjusted-visits per year. We interviewed leadership at 14 high APC and 16 low APC productivity CHCs to elicit organizational conditions that could explain the difference. Using content analysis and then qualitative comparative analysis, we found several important conditions were more common among high productivity CHCs, including scheduling APCs and physicians for the same number of visits, parity in terms of any financial incentives, and formal education programs for new APCs during onboarding/transition to practice.